QTL Mapping and Inheritance of Clubroot Resistance Genes Derived From Brassica rapa subsp. rapifera (ECD 02) Reveals Resistance Loci and Distorted Segregation Ratios in Two F2 Populations of Different Crosses - Fredua-Agyeman, Rudolph; Jiang, Junye; Hwang, Sheau-Fang; Strelkov, Stephen E. (Frontiers in Plant Science, 2020)
In this study, Brassica rapa subsp. rapifera (ECD 02) which exhibits broad-spectrum resistance to many Canadian Plasmodiophora brassicae isolates was crossed with two clubroot-susceptible B. rapa accessions and the B. napus cv. ‘Westar’ to produce three F2 populations. The F2 plants were screened against P. brassicae pathotypes 3H, 5X and 5G. The Chi-square goodness of fit test showed that the vast majority (≈ 90%) of the crosses that produced the F2 populations showed segregation ratios of 9R:7S, 5R:11S and 11R:5S. These were modifications of the 15R:1S ratio expected for the inheritance of two dominant major clubroot resistant (CR) genes from ECD 02. The distorted segregation ratios suggest that the two resistance genes are on different chromosomes and that two genes interact in an epistatic manner to confer resistance. Genotyping was conducted with 144 PCR-based markers in two of the three F2 populations. Linkage and QTL analysis with the polymorphic markers identified one and two QTLs on chromosome A03 to be associated with resistance to P. brassicae pathotype 5X and 5G, respectively. The QTLs clustered in genomic regions on the A03 chromosome of B. rapa where the CRa/CRbKato gene(s) are mapped. In addition, the Crr1 gene on the A08 chromosome of B. rapa was detected in the two populations. Therefore, the phenotypic and molecular data confirm the existence two CR genes in ECD 02. This is the first study that shows that major dominant genes in Brassica interact in a non-additive manner to confer resistance to different P. brassicae pathotypes.